Development of transmedia competences in high school students in Ecuador - Ibarra Núñez, Marcos Manuel; Ullauri Ullauri, Jaime; Abril Piedra, Hugo (EDMETIC, 2025)
The objective of this article is to present a synthesis of one of the results, a product of the research project called "Transmedia Education; transmedia competences and informal learning strategies of adolescents ", carried out by teachers of the National University of Education (UNAE), which was developed in the educational units of zone 6 of education in Ecuador, where it was possible to determine the development of transmedia competences and the informal learning acquired by high school students of the Ecuadorian educational system. The same ones that are developed with greater recurrence in secondary students at private high schools unlike students at state high schools, regardless of their geographical location, whether urban or rural